Salivary cortisol to assess stress in pigs - Martín, P.; Ovejero, I.; Mateos, A.; Villarroel, M. (Revista Complutense de Ciencias Veterinarias, 2013)
The first aim of the present study was to evaluate the measure ‘salivary cortisol’ as a non invasive Animal Welfare indicator for fattening pigs. The second objective was to assess the effect of a commercial farm routine procedure (weighing) in the HPA axis activation. The effect of the breading line (breeding line A and B), the sex, the date and hour of the sampling, and the different flooring systems used in the housing were taken into account. Two types of partly-slatted housing were used, continuous concrete floor and concrete slat (CC) and continuous solid floor of concreted recovered with epoxy resin and metallic slat (RM). Firstly, salivary control samples were taken in 1 pig per pen on three different days during fattening (morning and afternoon) for a total of 96 samples. Secondly, another salivary cortisol sample was taken after weighing each pig, 0h, 1h and 2h after weighing (stressful situation) near the end of fattening, in 3 pigs per pen, for a total of 144 samples. There were no differences in baseline cortisol levels for pigs on either flooring but, after the weighing, the cortisol level of the animals housed in the RM flooring were significantly lower (p
Keywords: Welfare; pigs; salivary cortisol.